2008
DOI: 10.1089/end.2008.0169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin-to-Stone Distance on Shockwave Lithotripsy Success

Abstract: Multiple variables have been shown to be associated with SWL success. In our sample of patients with preoperative CT scans, SSD was found to have no effect on SWL success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
2
10
2
1
Order By: Relevance
“…The efficacy of SWL was decreased in patients with higher serum creatinine concentrations in our study, which is compatible with other reports [29,30]. Lee et al.…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of SWL was decreased in patients with higher serum creatinine concentrations in our study, which is compatible with other reports [29,30]. Lee et al.…”
Section: Discussionsupporting
confidence: 93%
“…SSD as a predictor of SWL success remains controversial. Until recently, SSD was a significant factor in a half of published studies, and in the rest studies, there was no significant difference in SSD for success or stone-free rate after SWL [22][23][24][25][26][27]. In the present study, SSD was also not a significant predictor for one-session stone-free status after SWL.…”
Section: Discussioncontrasting
confidence: 58%
“…When the skin-to-stone distance is large, the stone cannot be positioned precisely at the focal point of the lithotripter without inverting the cushion of the treatment head—a situation almost certain to produce very poor coupling. Data on the trade-off between coupling and positioning of the stone along the axis of a lithotripter in obese patients have never been reported, although tellingly a recent study found no effect of skin-to-stone distance when using the HM3, a lithotripter for which coupling is not an issue 103. With many lithotripters, however, the stone can be broken even if it is positioned distal to the focal point 104.…”
Section: Other Challengesmentioning
confidence: 99%